Characterization of Optimal Carbon Nanotubes Under Stretching and Validation of the Cauchy–Born Rule - Friedrich, Manuel; Mainini, Edoardo; Piovano, Paolo; Stefanelli, Ulisse (Archive for Rational Mechanics and Analysis, 2019)
Carbon nanotubes are modeled as point configurations and investigated by minimizing configurational energies including two- and three-body interactions. Optimal configurations are identified with local minima and their fine geometry is fully characterized in terms of lower-dimensional problems. Under moderate tension, we prove the existence of periodic local minimizers, which indeed validates the so-called Cauchy–Born rule in this setting.
CRIS-Team Scopus Importer:2021-10-21